The Norton Field Guide to Writing - Bullock, Richard H. (W.W. Norton & Co., 2006)
Easy to use, flexible, and a great value—The Norton Field Guide to Writing is the most successful new rhetoric in a generation. Now in a second edition. With just enough detail — and color-coded links that send students to more detail if they need it — this is the rhetoric that tells students what they need to know and resists the temptation to tell them everything there is to know. The first rhetoric for easy reference, like a handbook—with menus, directories, and a glossary/index that make it easy to use—in a format that’s as user-friendly as the best handbooks. .